1979
DOI: 10.1111/j.1600-0714.1979.tb01618.x
|View full text |Cite
|
Sign up to set email alerts
|

Advances in epithelial kinetics—An oral view

Abstract: There is growing evidence that the basal layer of stratified squamous epithelia consists of cells of differing proliferative capacities and behaviour. These can be classified as stem cells transient amplifying cells and post‐mitotic maturing cells, the most important of which appear to be the stem cells which may be present throughout life and are responsible for all cell production under steady‐state conditions. Recent stem cell concepts are reviewed for epidermis, intestinal crypt and oral mucosa and are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 87 publications
4
37
0
Order By: Relevance
“…S2B–C). The evidences that these proliferating cells could undergo significant replication and expressed no differentiated markers suggests that these cells might be “transient amplifying cells” in the process of “stem cells→ transient amplifying cells→ terminally differentiated cells” [28]. Moreover, we demonstrated that several transcription factors critical for pancreatic progenitor development were also up-regulated in the islets of our P21 overexpression transgenic mice after STZ treatment (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…S2B–C). The evidences that these proliferating cells could undergo significant replication and expressed no differentiated markers suggests that these cells might be “transient amplifying cells” in the process of “stem cells→ transient amplifying cells→ terminally differentiated cells” [28]. Moreover, we demonstrated that several transcription factors critical for pancreatic progenitor development were also up-regulated in the islets of our P21 overexpression transgenic mice after STZ treatment (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…22 In 2002, Jarnbring et al studied the number of apoptotic and proliferative gingival keratinocytes in patients with gingivitis and in those with periodontitis with PCNA. [23][24][25][26] Monitoring the expression of PCNA, which is a polymerase-delta helper protein in DNA, provides valuable information about the reparative and regenerative potential of the cell. 10 As previous studies showed, the structure of DNA can be used to observe and evaluate the mitotic activity in the proliferating cell population.…”
mentioning
confidence: 99%
“…[2] [8] When a basal cell divides, both daughter cells may remain on the basement membrane, but an adjacent keratinocyte is displaced into the suprabasal layer and then enters into differentiation.…”
Section: Cell Replicationmentioning
confidence: 99%
“…[8] [14] It has been suggested that the basal keratinocytes with the flatter dermal interface, the so-called non-serrated basal cells, may in fact be stem cells. [3] The stem cells divide, thereby giving rise to transient amplifying cells.…”
Section: Cell Replicationmentioning
confidence: 99%